Energy Management Systems and Strategies in Buildings Sector: A Scoping Review - Al-Ghaili A.M.; Kasim H.; Al-Hada N.M.; Jorgensen B.N.; Othman M.; Jihua W. (Institute of Electrical and Electronics Engineers Inc., 2023)
Energy efficiency; Energy management; Forecasting; Control energy; Current problems; Energy performance; Energy-saving rates; Estimation and predictions; In-buildings; Scoping review; Sequential functions; Energy management systems